PERBANDINGAN KINERJA KEUANGAN PERBANKAN SYARIAH DAN PERBANKAN KONVENSIONAL DI INDONESIA DILIHAT DARI RASIO KEUANGAN DENGAN KERANGKA CAMEL - , RANI WIJAYANTI ([Yogyakarta] : Universitas Gadjah Mada, 2013)
The aim of this research was to compare the financial performance of syariah banking and conventional banking in Indonesia and to find out whether the slow growth of syariah banking in Indonesia was stem from the difference in their financial performance or not. This research used CAMEL frame to choose which ratios will be analyzed. Capital Adequacy Ratio (CAR) was used as a proxy for capital measurement, Non Performing Loan (NPL) for conventional banking and Non Performing Financing (NPF) for syariah banking was used as a proxy for asset quality measurement, Return on Asset (ROA), Return on Equity (ROE) and Biaya Operasional terhadap Pendapatan Operasional (BOPO) banking were used as a proxy for earning capacity measurement and Loan to Deposit Ratio (LDR) for conventional bank and Financing to Deposit Ratio for syariah banking was used for liquidity measurement. Time period was stem from 2007 until 2011 and those sample-bank were categorized into 3 groups. First group was for banks with asset from 10 Trillion until 55 Trillion, second group was for banks with asset from 1 trillion until 10 trillion and third group was for banks under 1 Trillion. Comparison was made for each ratio between sample from the same group and for overall data. Independent Sample t-test was employed to test those data with normal distribution and Mann whitney test was employed for data with abnormal distribution. In general, the study found no statistically significant difference in financial performance between Islamic banks and conventional banks, except in the NPL/NPF ratio for first group and LDR/FDR in second group.